Development of pH-responsive antioxidant soy protein isolate films incorporated with cellulose nanocrystals and curcumin nanocapsules to monitor shrimp freshness. (November 2021) - Xiao, Yaqing; Liu, Yingnan; Kang, Shufang; Cui, Mengdi; Xu, Huaide
Abstract: Spherical curcumin/polyvinylpyrrolidone nanocapsules (CurNC) with the improved water solubility and thermal stability than native curcumin (Cur) were synthesized. Subsequently, soy protein isolate-based pH-sensitive multifunctional packaging films reinforced with cellulose nanocrystals (CNC), CurNC, CNC/CurNC, and CNC/Cur were developed for shrimp freshness detection. It was found that adding the CNC-containing agents improved the tensile strength, hydrogen bond interactions, thermal stability, and crystalline structure of the film and decreased its water solubility and water vapor and oxygen permeability. The Cur-containing agents decreased the L* (lightness/darkness) and a* (redness/greenness) values and increased the b* (yellowness/blueness) and ΔE (total color difference) values of the film. A more dense and uniform matrix of the nanocomposite films was likely responsible for delaying the release of Cur from the film matrix. Interestingly, CNC/CurNC film displayed higher antiradical scavenging activity than CNC/Cur film, as well as remarkable color responsiveness to pH changes and NH3 presence. Moreover, the CNC/CurNC film was able to decrease the total volatile basic nitrogen of stored shrimp and visually monitor shrimp freshness in real-time. Graphical abstract: Image 1 Highlights: Curcumin nanocapsules (CurNC) had improved water solubility and stability than Cur. pH-sensitive antioxidant film based on soy protein isolate was developed. Cellulose nanocrystals (CNC) delayed the release of Yu et al., 2017, 2018 curcumin from film matrix. CNC/CurNC film showed good antioxidant activity and color response to pH and NH3 . The film loaded with CNC/CurNC can visually monitor shrimp freshness in real-time.